Do Nonresident Students Affect Prices for In-State Students at Public Colleges?. Issue 2 (February 2019) - Kelchen, Robert
Background/Context: Public colleges and universities have sought to recruit and enroll more students from outside their home state in an effort to both enhance institutional prestige and generate additional revenue from the higher tuition rates than nonresident students generally pay. A body of research has shown that nonresident students tend to be more economically advantaged and less racially diverse than in-state students and that increases in out-of-state students crowd out lower income and minority state residents from more selective public colleges. Purpose/Research Questions: Although research has shown some adverse effects of additional nonresident enrollment, no prior research has examined whether the additional money generated from out-of-state students' higher tuition rates is used to help make college more affordable for state residents. In this article, I examined whether increased percentages of nonresident students were associated with changes in the sticker or net prices of attendance at four-year public colleges and whether any relationships were different between broad-access and selective public colleges. Research Design: I used data on college pricing and nonresident enrollment from the U.S. Department of Education's Integrated Postsecondary Education Data System from the 2000– 01 through 2013–14 academic years from 505 public four-year colleges in this analysis. I used panel regressions with controls for other state-level factors that could have affected nonresident enrollment. In my preferred specifications, I used Arellano–Bond estimators to account for autoregressive processes in the data and used a one-year lag between nonresident enrollment and when prices paid by in-state students were measured. Results and Conclusions: There was no systematic relationship between changes in the percentage of nonresident students and the sticker or net prices faced by in-state students. This suggests that although state residents do not appear to be subsidizing an amenities arms race to attract students from other states, the additional tuition revenue coming from nonresident students is not being used to help subsidize in-state students. Future research should investigate how public colleges are using the additional revenue if it is not being used for student financial aid.